Modeling sorghum yield response to climate change in the semi-arid environment of Ethiopia - Gardi, Mekides W.; Zewdu, Eshetu; Sida, Tesfaye Shiferaw (Elsevier, 2025)
In Ethiopia, sorghum is a vital food security crop, predominantly cultivated in semi-arid, rain-fed agricultural landscapes. However, the increasing effects of climate change now present a serious threat to its sustainable production. This study assessed the impacts of climate change on three popular sorghum varieties (ESH-1, ESH-2, and Melkam) in three semi-arid areas of Ethiopia using a crop-climate modeling approach. Calibration and validation of the CERES-Sorghum model demonstrated strong agreement between simulated and observed values, confirming its reliability for application. Climate projections from three GCM models show temperature increases up to 2.1 °C by the 2050s and 4 °C by the 2080s. Rainfall changes varied by location, with Mieso projected for a 21.8 % increase and Melkassa showing minimal change but high variability. Our findings reveal highly differential and location-specific yield responses across varieties under projected climate. Although projections show Kobo yields remaining stable or increasing slightly under climate change, sensitivity analysis reveals potential yield declines of up to 44 % with a 20 % rainfall reduction. In contrast, projections for Melkassa showed consistent yield declines across all varieties, exhibiting strong sensitivity to temperature changes, where a 1.5 ∘C increase potentially reduces yields by up to 40 %. In comparison, Mieso displayed mixed responses, with the ESH-2 variety performing notably better under future scenarios. These findings suggest that current agronomic practices may be insufficient to sustain yields under climate scenarios, threatening future food security. Thus, developing and implementing climate-resilient strategies, including cultivating drought-tolerant sorghum cultivars, optimizing irrigation, and enhancing soil health, is crucial to ensure effective adaptation and regional food security.